(untitled) (Marketing Journal, 2025)
The article highlights the peculiarities of the implementation of an environmental management system in the economy of enterprises, including the specifics of the process of introducing management practices aimed at minimizing the environmental impact of t he enterprise. This process involves adapting the economic activities of the enterprise to environmental requirements. In particular, the enterprise tries to achieve economic efficiency in its activities along with compliance with environmental norms, whil e the introduction of environmental management requires the adoption of modern and environmentally friendly technologies, as reflected in this article. 211